Studi Kasus Perilaku Maladaptif pada Anak Usia Sekolah Dasar: Analisis Intervensi Sosial di PPSPA Bima Sakti Batu - Sholikhul Huda; Denok Setiawati; Najlaytun Naqiyah (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
Childhood is a crucial phase of development in shaping an individual's behavior and personality. However, not all children are able to adapt to the demands of their social environment in an adaptive manner. This study aims to identify maladaptive behaviors in elementary school-aged children, analyze the contributing factors, and examine the social intervention efforts undertaken by child protection agencies. The study employs a qualitative approach using a case study method on a 9-year-old boy (AR) who is undergoing a probationary period at PPSPA Bima Sakti Batu due to exhibiting deviant behavior. Data collection techniques include observation, semi-structured interviews, and documentation. The results of the study indicate that AR exhibits various forms of maladaptive behavior, such as stealing, truancy, aggressive behavior, using coarse language, and displaying extreme tantrums. The primary causal factors stem from permissive parenting styles and emotional neglect by the parents. At the PPSPA institution, AR also faces difficulties in adaptation, lack of discipline, and social conflicts with peers. The social interventions implemented included social worker accompaniment, rule enforcement, and coordination with family members and relevant government agencies. The conclusion of this study is that maladaptive behavior in children is not only caused by internal factors but is also strongly influenced by interaction patterns within the family and social environment. Effective interventions require a holistic and collaborative approach to ensure that behavioral change processes can occur sustainably.